Structural and defect changes in black carbon charcoal irradiated with gamma ray - Almugren, K.S.; S.F. Abdul, Sani; Irzwan Affendy, sulong; S.N. Mat, Nawi; A.S. Siti, Shafiqah; Bradley, D.A. * (Elsevier, 2022)
This study investigates the use of black carbon charcoal as passive radiation dosimetry, offering low dependence on photon energy and near soft tissue effective atomic number with state-of-the-art techniques. Regression analyses have now been conducted using graphite manufactured commercially in the form of charcoal from three different types: mangrove, coconut, and green charcoal recycled from sawdust, working with photon-mediated interactions at radiotherapy dose levels. Explorations of changes in Raman spectroscopic characteristics, and photoluminescence dose dependence have been performed with a focus on the relationship between absorbed radiation energy and induced material changes, using a 60Co gamma-ray source doses ranging from 0 to 10 Gy. Raman spectroscopy has established to be an effective method for exploring defects in carbon-based materials due to its high sensitivity, most commonly focusing on the use of ID/IG parameter. While photoluminescence analysis will provide information on electronic properties and the band gap energy. The crystal structure of the black charcoal samples was characterised using X-ray diffractometry, with the goal of determining the degree of structural order, atomic spacing, and lattice constants of the various irradiated charcoal samples, supported by crystallite size assessments. The findings of this study could pave the way for a low-cost yet highly effective system for studying radiation-induced changes in carbon, as well as offering a viable alternative to current commercial dosimeters, well suited to applications in radiotherapy.